Pelatihan Penerapan Fungsi-fungsi Manajemen dalam Pengelolaan Organisasi pada Pengurus Majelis Taqorrub Ilallah (MTI) - Fatoni, Aris; Setiawan, Iwan; Faisal, Andri (Lembaga Penelitian Dan Pengabdian Pada Masyarakat (LPPM) Institut Bisnis dan Informatika (IBI) Kosgoro 1957, 2020)
This Community Service Activity (PKM) was conducted at the management of the Majelis Taqorrub Ilallah (MTI) having its address at Jl. Walet No. 101 RT. 06 RW. 02 Mekarsari Kec. Tambun Selatan Kab. Bekasi 17510, with the aim of increasing managerial knowledge and skills in managing the organization, so that it can become an organization that has good governance that is professionally managed and provides greater benefits to the community. The method of implementing activities uses the Training and Mentoring method with the stages of activity: 1) Presentation of management functions: planning as well as vision-mission preparation training, 2) Presentation of organizing management functions, actuiting, and controlling, 3) Mentoring in planning and implementing activities with training to make pamphlets to be published on social media, 4) Mentoring in the form of Team Management Training. The PKM output is the determination of the target audience on the vision and mission of the student, student and employee segments, the formation of a new organizational structure, by forming three divisions to strengthen the targeted segment, namely high school students, students and employees, and pamphlets for publication activities in the media social. The results of this PKM activity can improve the managerial knowledge and skills of the management in managing the MTI organization.